Advanced Introduction to National Innovation Systems - Chaminade, Cristina; Lundvall, Bengt -Ake; Haneef, Shagufta (Cheltenham Edward Elgar Publishing Ltd., 2018)
"Innovation studies is an evolving interdisciplinary field that has moved away from the weaknesses of neoclassical thinking and embraced evolutionary theory. In this timely book, the authors offer a precise introduction to the nature of national innovation systems (NIS), examining the history of the concept and its use in todays world.This book uses language appropriate for both social science and engineering scholars to offer an accurate synopsis of the emergence of the concept, its theoretical core and its evolution. It analyses both developed and developing countries in terms of their NIS and its application to current societal challenges, such as economic growth, inclusive development and environmental sustainability, in an increasingly globalized and interconnected world. Key features include:.Three authors from three different generations and countries offer an overview of NIS from around the world. Extensive use of examples from the Global North and Global South. Recommended in-depth reading after each topical chapter. Overview of future research challenges•up-to-date review of the literature and engagement in current debates.Erudite and accessible, this unique book on NIS can easily be used for undergraduate and graduate teaching. It is a valuable, and much-needed resource for teachers, students and researchers at all levels."--Publisher's description.--Publisher's description
​1. Introduction -- 2. The origin and the early evolution of the national innovation systems concept -- 3. The theoretical core of the national innovation systems concept -- 4. How to analyse national innovation systems - the qualitative approach -- 5. How to analyse national innovation systems - the quantitative approach -- 6. National innovation systems and economic development -- 7. National innovation systems and inclusive development -- 8. National innovation systems and environmentally sustainable development -- 9. Innovation policy and national innovation systems -- 10. Globalization of innovation and national innovation systems -- 11. Challenges for the research on national innovation systems
Includes bibliographical references (p. 151-167) and index
Keywords: Economic development; ECONOMIC DEVELOPMENT; TECHNOLOGICAL INNOVATIONS; ECONOMIC ASPECTS; SUSTAINABLE DEVELOPMENT